Avaliação da qualidade de vida urbana dos discentes da Universidade Federal de Santa Maria residentes no município por meio da regressão logística - Ricci, Mayara Rohenkohl (2019)
The urban environment differs from one city to another and, by itself, already makes it an important subject to be analyzed, another fact is that cities are developing more and more, leading, consequently, to the growth of population. And so that there is no retrograde welfare process for the population, there is a need to initiate studies aimed at this area. Considering the relevance and the contributions of the theme, this study has the purpose of analyzing the perception of UFSM students and identify factors associated with the quality of urban life in the municipality of Santa Maria. A total of 5949 (21.78%) students of the Federal University of Santa Maria, residents of the municipality, were interviewed, who answered in a single question (QVU1) about the general satisfaction of the housing neighborhood, and also considering several issues grouped in (QVU2), through an instrument created based on the IQVU-BR (Urban Quality of Life Index of Brazilian municipalities), which considers topics such as infrastructure, environment, education, health, among others. A descriptive analysis was carried out and logistic regression models were adjusted for both situations (QVU1 and QVU2), considering as a result the fact that the student is or is not satisfied with the housing neighborhood as a function of covariables investigated. It was observed that the majority of the respondents were female (3595; 60.43%), aged 16 to 26 years (3909; 65.71%), unmarried (4543; 76.37%) and without declared income (2566; 43.13%). The highest participation was of the undergraduate students (3032; 50.97%), followed by the undergraduates (1088; 18.29%) and masters (749; 12.59%). In general, 4485 (75.4%) of the students reported satisfaction with the housing neighborhood, with the majority of women (76.91%). However, this percentage reduces when one considers the various issues broken down by theme. For the model, considering general satisfaction, it was observed that gender (OR=1.23), civil status (Married: OR=1.45), income (OR=1.18), academic level (OR=1.25) and neighborhood (Camobi: OR=0.64, others: OR=0.52) were significantly associated with satisfaction with quality of life in the housing neighborhood. For the second model, the associations were significant with gender (OR=0.70), neighborhood (Camobi: OR=0.60; others: OR=0.44), work (OR=0.86) for more than three years in the neighborhood (OR=0.60). Thus, it was possible to establish associated factors and estimate probabilities of satisfaction with the housing neighborhood, according to some characteristics of the students, enabling the responsible managers to evaluate the possibility of improvements in the identified vulnerable aspects.